Cardiac doses with deep inspiration breath hold in breast cancer radiotherapy: direct comparison between WBI, PBI, and interstitial APBI - Sirak, Igor; Pohanková, Denisa; Kašaová, Linda; Hodek, Miroslav; Motyčka, Petr; Asqar, Ahmed; Grepl, Jakub; Paluska, Petr; Novotná, Veronika; Vosmik, Milan; Petera, Jiri (Reports of Practical Oncology and Radiotherapy, 2024)
BACKGROUND: The optimal radiotherapy technique for cardiac sparing in left-sided early breast cancer (EBC) is not clear. In this context, the aim of our dosimetric study was to compare cardiac and lung doses according to the type of radiotherapy - whole breast irradiation (WBI), external partial breast irradiation (PBI), and multicatheter interstitial brachytherapy-accelerated partial breast irradiation (MIB-APBI). The dosimetric results with the WBI and PBI were calculated with and without DIBH. MATERIALS AND METHODS: Dosimetric study of 23 patients treated with WBI, PBI, with and without DIBH, or MIB-APBI. The prescribed dose was 40 Gy in 15 fractions for WBI and PBI and 34 Gy in 10 fractions (bid) for MIB-APBI. Doses to the organs-at-risk (OAR) - heart, left anterior descending coronary artery (LAD), left ventricle (LV), and left lung - were recalculated to the equivalent dose in 2-Gy fractions (EQD2). RESULTS: The addition of DIBH significantly reduced EQD2 doses to all OARs (except for the left lung maximal dose) in WBI and PBI. MHD values were 0.72 Gy for DIBH-WBI, 1.01 Gy for MIB-APBI and 0.24 Gy for DIBH-PBI. There were no significant differences in cardiac doses between WBI with DIBH and PBI without DIBH. DIBH-PBI resulted in significantly lower mean doses to all OARs (except for maximum lung dose) compared to MIB-APBI. Conclusions: These results show that the use of DIBH significantly reduces cardiac doses in patients with left EBC. Partial irradiation techniques (PBI, MIB-APBI) significantly reduced cardiac doses due to the smaller clinical target volume. The best results were obtained with DIBH-PBI.